10.61533 EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL TERHADAP PERSEDIAAN BARANG DAGANG DI CV MM ACING JAYA TUATUNU PANGKALPINANG - Sherly Tabita, Jessintha; Oktalina, Gayatria; Novika (STIE IBEK Pangkalpinang, 2024)
This thesis, written and compiled by Jessintha Sherly Tabita with Student Identification Number 540200024, is titled “Effectiveness of the Internal Control System on Merchandise Inventory at CV MM Acing Jaya Pangkalpinang.